Application Model Da'wah Sunan Bonang (Raden Maulana Makdum Ibrahim) on Cottage Islamic boarding school College student Jagad 'Alimussirry Surabaya - Aisyah, Siti (Journal Intellectual Sufism Research (JISR), 2019)
Da'wah is something that should be done by Muslims, where da'wah has the purpose of forming a better character and personality that is able to grow a soul that has a moral character. There are various kinds of da'wah methods, one of which is da'wah carried out by Walisongo. Walisongo built a pesantren in carrying out his preaching namely sunan bonang with Sufism-based ahlusunnah waljamaah pesantren. The existence of Islamic boarding schools in Surabaya can also make the surrounding communities take part in following the teachings delivered by each study. Every santri is also able to preach to the surrounding community and this is a process of developing da'wah. Sufism-based ahlusunnah waljamaah Islamic boarding school is located in the Jagad mahasiswa Alimussirry Surabaya student boarding school. There are similarities used by the sunan Bonang and Jagad im Alimussirry boarding schools in preaching so that they become research. This type of research is a qualitative research method. The research location was centered at the Jagad Islamic Boarding School ‘Alimussirry Wonokromo Surabaya. In this study, it shows that there is an equation of tariqah used by Sunan Bonang with the Islamic Student Ponpes ‘Alimussirry Surabaya in preaching through Islamic boarding schools.